Integration Of Religious Moderation Values In The Learning Of The Quranic Text History - Emawati, Emawati; Sany, Ulfi Putra (LP2M IAIN kUDUS, 2025)
Religious moderation is considered a solution to stem radicalism and extremism, particularly in higher education environments. This research aims to determine students' needs for integrating moderation values into learning and to understand their perceptions of the integration of religious moderation values in the History of the Qur'an. This research aims to develop a curriculum model and teaching materials for the course that incorporate Islamic moderation. This research method employs the Research and Development (R&D) model, utilizing the ADDIE (Analyze, Design, Develop, Implement, Evaluate) approach. The initial stage focuses on needs analysis. We collected data through the distribution of questionnaires and interviews with 30 students and lecturers teaching the History of the Qur'an course at the State Islamic University of Salatiga. The results of the study show that many students (71.2%). They view religious moderation as very important to life and advocate its integration into lecture materials. All lecturers (100%) should use religious moderation material, and 80% acknowledged the urgency of textbooks; however, no one has prepared a special textbook with moderation content for this course. The needs analysis reveals that students require textbooks that incorporate the concept of moderation, which is easy to understand (with the aid of concept maps/summaries), and align with the applicable KKNI curriculum.